Propuesta de un plan de seguridad hídrica en la junta administradora de agua potable san felipe, cantón mocache, provincia los ríos, ecuador - Zarate Guerra , Ariel Francisco (2024)
The Potable Water Management Board "San Felipe" is facing significant challenges regarding water supply. In response to this situation, a detailed water security plan has been developed with the aim of improving resource management within a three-year timeframe. This plan is based on a comprehensive methodology that includes a diagnosis through checklists, interviews with operational staff, and user satisfaction surveys. Additionally, laboratory analysis of microbiological and physicochemical parameters is conducted to identify associated hazards and quantify risks, as well as the development of proposals to address high-risk hazardous events. The diagnostic results have shown significant deficiencies in water treatment, the presence of clandestine connections compromising the quality and quantity of supply, and financial constraints hindering the implementation of improvements. User perception of water quality and communication with the Management Board demonstrated the importance of transparency and community participation in water resource management. Physicochemical and microbiological analyses identified parameters above standard levels, indicating that according to ICA NSF, the water from the board is relatively of poor quality. This underscores the urgency of implementing corrective measures to ensure a safe and reliable supply of potable water for "San Felipe" users. The proposed water security plan includes measures such as modernizing the supply system infrastructure, comprehensive risk management, and active involvement of experts and community members in decision-making. The ultimate goal is to ensure a safe, sustainable, and quality supply of potable water for all users.